ANALISIS KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL LOMPAT TALI PADA ANAK TUNAGRAHITA BERAT: ANALYSIS OF GROSS MOTOR SKILLS THROUGH TRADITIONAL JUMP ROPE GAMES IN CHILDREN WITH SEVERE INTELLECTUAL DISABILITIES - Ngaisah, Nur Cahyati; Naimah, Naimah; Putro, Khamim Zarkasih (Thufuli, 2023)
Mentally retarded children in the idiot category tend to experience delays in several aspects of ability, one of which is gross motor skills. This is influenced by mentally retarded children who are passive and rarely do movement activities so that the muscles, brain and nerves do not coordinate optimally. Optimizing children's motor skills can be done through activities that are popular with children which contain a lot of movement in their activities, one of which is through the traditional game of jumping rope in training three basic movement categories namely locomotor, non-locomotor and manipulative. The purpose of this study was to describe the development of the motor skills of mentally retarded children in the severe category through the traditional game of jumping rope which was carried out at the Darma Rena Ring Putra II SLB-C school. The research method uses a qualitative approach with data collection techniques through observation and interviews. Data analysis techniques namely data reduction, data presentation, drawing conclusions by testing the validity of the data using triangulation techniques. The results of the study showed that the gross motor skills of children with severe mental retardation could be stimulated using the traditional jump rope game which optimally creates various kinds of body movements. So that it can train children to perform various kinds of movements with confidence and have the courage to do so, such as walking, running, lifting one leg, and jumping.